Assessing of ESG Scores on Carbon Performance: Moderating Role of Board Independence - Novy Fajriati; Dini Wahjoe Hapsari (Jurnal Akuntansi, 2026)
This study is motivated by the rising levels of carbon emissions and the increasing importance of ESG practices as mechanisms for enhancing corporate environmental performance. It investigates whether board independence moderates the relationship between ESG scores and carbon emission performance, using panel data from 81 companies listed on the Indonesia Stock Exchange between 2022 and 2024 and secondary data are obtained from the Refinitiv Eikon database. The study applies moderated regression analysis, estimated using EViews. The results indicate that ESG scores have a significant positive impact on carbon emission performance, suggesting that higher ESG scores are associated with improved carbon outcomes. In contrast, board independence has a negative effect. Additionally, board independence does not significantly moderate the relationship between ESG and carbon emission performance, implying that it is an inadequate governance mechanism for strengthening the impact of ESG practices.